Correlation between Anthropometric Measurement and Kidney Function in the Elderly to Detection of Chronic Kidney Disease - Debie Anggraini; Prima Adelin (Indonesian Association of Clinical Pathologist and Medical laboratory, 2023)
Chronic Kidney Disease (CKD) is a very common clinical problem in elderly patients and is associated with increased morbidity and mortality. The proportion of the elderly is predicted to further rise to 20% by the year 2030 caused by the demographic change from a pattern of high birth rates and high mortality to low birth rates. Delayed mortality has contributed to the rise in the elderly population. The aging process involves physiological and nutritional changes that will affect the nutritional status of the elderly, leading to malnutrition and overweight. Aging is associated with considerable changes in body composition, higher BMI is associated with improved survival in patients with CKD and very low BMI levels have been consistently associated with high all-cause mortality in the elderly. The changes in Body Fat Percentage (BFP) in the elderly will affect the estimated Glomerular Filtration Rate (eGFR) in the elderly. This study aimed to determine the correlation between anthropometric measurement and kidney function in the elderly population. this research is an analytic observational study with a cross-sectional design, which involved 42 elderly people with age > 60 years in Guguak District, West Sumatera, Indonesia. Anthropometric measurement using the Waist-to-Height-Ratio (WHtR) method, Waist-to-Hip Ratio (WHR), Waist Circumference (WC), and Body Mass Index (BMI) and eGFR were calculated using the Cockcroft and Gault formula. The results of this study showed that the mean age of the elderly was 68±7.58 years, which consisted of 29.3% male and 70.7% female. The Pearson correlation test between WHR and eGFR obtained p<0.05 with r= 0.439 and the Pearson’s correlation test between BMI and eGFR obtained p<0.05 with r= 0.425. There was a moderate correlation between WHR with eGFR and BMI with eGFR in the elderly population.